Knowledge Sharing Driver in Virtual Community : A Systematic Review - Satria, Deki; Hendrawan, Satya Arisena (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2019)
Virtual community is one of the most used platforms to share knowledge. Virtualcommunity usually composed by people who shared vision or specialty in certain aspect. This paper is systematic literature review using PRISMA. The goals of this papers is to find what is the driving factor of the people to share their knowledge in this kind of community. The end result of this papers is driving factors which can be used to create knowledge sharing model in virtual community.